Mentalization-based intervention to recurrent acute presentations and self-harm in a community mental health service setting. (June 2015) - Bosanac, Peter; Hamilton, Bridget; Beatson, Josephine; Trett, Robert; Rao, Sathya; Mancuso, Sam; Castle, David
Objectives: A proof-of-concept study over an 18-month period to determine whether a mentalization-based intervention (MBI) in a metropolitan community mental health service, when added to a recovery-based model of care, would be of clinical benefit to borderline personality disorder (BPD) consumers with a history of recurrent, deliberate self-harm. The feasibility of implementing the intervention, and factors that could improve its implementation, will be evaluated. Methods: Three-monthly focus groups with participating community mental health service case managers ( N = 8) assessed the implementation and the impact of an MBI added to a recovery model of care and the way the clinicians worked with consumers with BPD and recurrent, deliberate self-harm in this context. Results: Qualitative analysis revealed compatibility of the MBI with a recovery-based case management approach for the above group of consumers, albeit with operational barriers. Conclusions: MBI with consumers with BPD appears to be compatible with recovery-focused psychiatric case management and was accepted by consumers. The case managers perceived that no harm was rendered in terms of deliberate self-harm and acute service utilization. The MBI led to a sense of improved therapeutic alliance in case managers working with consumers.